Complete histologic response to chemotherapy in a patient with a mediastinal yolk sac tumor: a case report - Akasbi, Yousra (BMC Res Notes, 2014)
BACKGROUND: Malignant mediastinal germ cell tumors are a rare disease and represent only 1% to 4% of all mediastinal tumors. Gonadal germ cell tumors are generally the most common type and constitute 90% of germ cell tumors. The mediastinum is the second most frequently affected area ahead of other extragonadal areas, which include the retroperitoneum, the sacrococcygeal area, and the central nervous system. We report on the case of a mediastinal yolk sac tumor with a complete histological response to chemotherapy. CASE PRESENTATION: A 26-year-old Moroccan man, without a medical or surgical history, presented with a four-month history of chest distress, dyspnea, and a frequent dry cough for the previous month. A computed tomographic scan of the chest revealed a bulky mediastinal mass, which was biopsied. Histologically, the tumoral mass proved to be a yolk sac tumor. The serum level of alpha-fetoprotein of this patient was elevated to 19052 ng/ml. After 4 courses of preoperative chemotherapy, the patient underwent a surgical resection of the tumor, with a complete pathologic response. At the time of writing, the patient is alive with complete remission without any evidence of recurrence. CONCLUSION: Primary mediastinal Yolk sac neoplasm represent a unique entity, and as such require specialized management. The diagnosis should be made not only by morphological studies but the patient’s age and the elevation of serum alpha-fetoprotein should also be considered. The utilization of cisplatin-based chemotherapy is associated with the best chance of a cure for this disease. This should be followed by surgical resection of the residual tumor in the nonseminomatous germ cell tumor.